Making Sense of Africa's Emerging Digital Transformation and its Many Futures. (2nd October 2017) - Ndemo, Bitange; Weiss, Tim
Abstract : Digital technologies have spread across the African continent at an inexorable pace. Widely cited data on adoption rates suggest that digital technologies are making their way into every facet of life in African societies — a broader change process cast in this paper as digital transformation seems to be underway. We look beyond adoption rates and examine actions that bring about favorable economic, organizational, political, social, and cultural environments which digital technologies depend on to realize their transformative potentiality. In our view, pure adoption does not indicate any broader change or transformation but rather indicates a potentiality for change — a latent power to catalyze broader societal change processes. In this paper, we develop a framework to make sense of Africa's emerging digital transformation. In so doing, we elaborate on the multiple environments that digital technologies are embedded in and, by extension, the multidimensional change processes they need to ignite. The goal is to provide a better understanding — and new avenues for research — why actions and changes in some environments tend to more readily embrace the new possibilities offered by digital technologies while others seem disconnected and are lagging behind.